DETERMINAN PRODUKTIVITAS KARYAWAN PADA PT. PERKEBUNAN NUSANTARA III AFDELING V MARPINGGAN - Santi Wahyuni; Budi Gautama Siregar; Aswadi Lubis; Damri Batubara (Jurnal Mahasiswa Akuntansi Samudra, 2022)
The level of employee productivity at PT. Perkebunan Nusantara III (Persero) Afdeling V Marpinggan, there are still employees who cannot achieve the targets of what the company has mandated to them both in terms of discipline, efficiency and encouragement of the employees themselves in carrying out their work. In supporting this research problem, the researcher raised the theory of work productivity, employee motivation, age and level of education of employees. This type of research is associative with quantitative data that is primary data. The respondents of this study were employees of PT. Perkebunan Nusantara III (Persero) Afdeling V Marpinggan, totaling 30 employees. Data were obtained through the distribution of questionnaires, interviews and documentation. Data processing was carried out with the help of the SPSS application and then analyzed for validity, reliability, normality test, classical assumption test, multiple regression analysis and hypothesis testing. The study found that employee motivation had a positive and significant effect on employee productivity while age and education level had no effect on employee productivity at PT. Perkebunan Nusantara III (Persero) Afdeling V Marpinggan